The future of the "European Consensus on Development - Thomas Henökl; Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
In view of the currently increasing demands and expecta¬tions of Europe, the question arises as to how the EU can perform its role as a global actor better and more effectively. The dramatic escalation of events in Europe's Neighbourhood and the subsequent refugee crisis in numerous member states (MS) clearly illustrate that a rethink of EU foreign and development policy is re¬quired. The EU was one of the most heavily engaged parties during the negotiations leading to the 2030 Agenda for Sustainable Development and in 2016 will need to address the challenge of implementing this agen¬da both within and outside Europe. In June 2015 EU High Representative for Foreign Affairs Mogherini launched a process of consultation aimed at establishing an EU Global Strategy by early summer 2016 that all member states can agree on. A value-based and sustainable development policy that also takes account of the Sustainable Development Goals (SDGs) should occu¬py a key position in such a strategy. The European Con¬sensus on Development Policy can no longer exist as an isolated document, but should instead be linked to other strategies of EU foreign policy. Building upon the premise that European development cooperation will assume an appropriate role in the Global Strategy and in a reformed 'Europe 2030 Strategy', the Commission and European External Action Service (EEAS) have begun thinking about a possible reform of the European Consensus on Develop¬ment. On 28 January 2016 Development Commissioner Neven Mimica informed the European Parliament (EP) that preparations for this have been underway since the informal Council of Ministers meeting of December 2015. The above context calls for a comprehensive review and reform of the European Consensus on Development (hereafter: the Consensus). This briefing paper looks into the past role and contributions of the Consensus in European development cooperation policy and operations and assesses the central challenges and opportunities for revising the Consensus and ensuring its continuing relevance. The improvement of coordination and coopera¬tion between humanitarian, development and neig¬hbour¬hood policy could indicate new paths and approaches in this regard. Four recommendations for reforming the consensus are derived from this analysis: Utilising the reform momentum for a rethink of the Consensus and the forthcoming negotiation on the future cooperation between the EU and the African, Caribbean and Pacific Group. Adoption of a holistic and sustainable security concept acknowledging the central importance of sustainable development in both Consensus and Global Strategy. Synergies through the closer integration of policy areas within as well as between MS and EU in the coordi¬nation of humanitarian aid and development policy. Definition of priorities for future cooperation with middle-income countries (MICs) and emerging powers.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Agenda 2030